ERROR PRODUCTION OF SPEECH BY THE SEVENTHSEMESTER STUDENTS OF ENGLISH DEPARTMENT FKIP UKI TORAJA - Alfrida Pasolang (Teaching English as a Foreign Language Overseas Journal, 2016)
Error Production of Speech by the Seventh Semester Students of EnglishDepartment of FKIP UKI Toraja. Thesis English Department Teacher Training andEducation Faculty, Christian University of Indonesia Toraja.The objective of this research is to find out the error production of speech are made bythe seventh semester students of English department of FKIP UKI Toraja.In order to achieve the objective of this research, the writer used qualitative method.The population of this research was the Seventh semester students of Englishdepartment academic 2015/2016, which consists of 207 and divided into 9 classes. Thesample of this research was 10 students. This research employed a random samplingtechnique. The data obtained from oral test by recording and then analyzed into thetable.The result of the data analysis shows that the seventh semester students of Englishdepartment of FKIP UKI Toraja still made error of speech production. This can beproved by the result of recording is error of silent pause with frequency 17, error offilled pause with frequency 10, error of repeats with frequency 15, error of correctionwith frequency 18, error of stutter with frequency 17, and error of interjection withfrequency 18.Based on the result analysis data above, the writer can conclude that the seventhsemester students of English department of FKIP UKI Toraja is still made error ofspeech production.